Aerobic Interval Training and Probiotic Supplementation Modulate Intrinsic Apoptosis-Related Gene Expression in the Myocardium of Rats with Myocardial Infarction - Miri Reykandeh, Sayed Touraj; Eftekhari Gheinani, ‌Elham; Banaei Borojeni, Jamshid (Health Nexus, 2026)
Myocardial infarction (MI) promotes mitochondrial dysfunction, oxidative stress, and cardiomyocyte loss, partly through activation of the intrinsic apoptotic pathway. Exercise training and probiotics may each influence these processes, but evidence concerning their combined effects is limited. This controlled animal study examined the effects of aerobic interval training (AIT), Lactobacillus acidophilus supplementation, and their combination on myocardial expression of Apaf1, Bax, Bcl2, Casp9, and Casp3 and on the Bax/Bcl2 expression ratio. Forty-eight male Wistar rats (250 ± 30 g) were allocated to six groups (n = 8 each): healthy control, sham surgery, MI, MI + AIT, MI + probiotic, and MI + AIT + probiotic. MI was induced by permanent ligation of the left anterior descending coronary artery. The interventions continued for 10 weeks; AIT was performed five sessions per week, and the probiotic was administered daily at 10^9 colony-forming units/mL. Left ventricular tissue was collected 48 h after the final intervention. Relative mRNA expression was quantified by real-time polymerase chain reaction and analyzed using one-way analysis of variance followed by Tukey testing. Significant group effects were detected for all outcomes (P < 0.001; η² = 0.79–0.89). Compared with healthy controls, MI increased Apaf1, Bax, Casp9, and Casp3 expression, reduced Bcl2 expression, and markedly increased the Bax/Bcl2 ratio. Both interventions attenuated these changes. The combined intervention produced the values closest to control levels, reducing Apaf1, Bax, Casp9, Casp3, and the Bax/Bcl2 ratio by approximately 62%, 63%, 62%, 63%, and 87%, respectively, relative to untreated MI, while increasing Bcl2 expression. These findings indicate that AIT and probiotic supplementation, particularly when combined, are associated with a less pro-apoptotic myocardial gene-expression profile after experimental MI. Because only mRNA outcomes were assessed, protein-level, functional, and clinical confirmation is required.